A dowry of blood - Gibson, S. T. (Redhook, 2022)
"A Dowry of Blood is a saga of obsession, desire and the lengths we will go to protect the ones we love. Saved from the brink of death by a mysterious stranger, Constanta is transformed from a medieval peasant into a bride fit for an undying king. But when Dracula draws a cunning aristocrat and a starving artist into his web of passion and deceit, Constanta realizes that her beloved is capable of terrible things. Finding comfort in the arms of her rival consorts, she begins to unravel their husband's dark secrets. With the lives of everyone she loves on the line, Constanta will have to choose between her own freedom and her love for her husband. But bonds forged by blood can only be broken by death."--